A Land of Milk and Honey with Streets Paved with Gold : Do Emigrants Have Over-Optimistic Expectations about Incomes Abroad? - McKenzie, David; Gibson, John; Stillman, Steven (World Bank, Washington, DC, 2012)
Millions of people emigrate every year in search of better economic and social opportunities. Anecdotal evidence suggests that emigrants may have over-optimistic expectations about the incomes they can earn abroad, resulting in excessive migration pressure, and in disappointment among those who do migrate. Yet there is almost no statistical evidence on how accurately these emigrants predict the incomes that they will earn working abroad. In this paper the authors combine a natural emigration experiment with unique survey data on would-be emigrants' probabilistic expectations about employment and incomes in the migration destination. Their procedure enables them to obtain moments and quantiles of the subjective distribution of expected earnings in the destination country. The authors find a significant underestimation of both unconditional and conditional labor earnings at all points in the distribution. This underestimation appears driven in part by potential migrants placing too much weight on the negative employment experiences of some migrants, and by inaccurate information flows from extended family, who may be trying to moderate remittance demands by understating incomes.